Analisa Yuridis atas Pelaku Tindak Pidana Penggelapan Ditinjau dari Pasal 372 Kitab Undang-Undang Hukum Pidana - Zulkipli; Maman Suparman (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2025)
Especially regarding embezzlement, which is regulated in chapter XXIV, article 372 to article 377 of the Criminal Code as follows